2015
DOI: 10.3390/molecules200713313
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Penetrating Peptides: Possibilities and Challenges for Drug Delivery in Vitro and in Vivo

Abstract: Abstract:In this review, we discuss how cell-penetrating peptides (CPPs) might get access to their intracellular targets. We specifically focus on the challenge of deciding whether the positively-charged CPPs are just bound to the negatively-charged cell surface and subsequently endocytosed or actually transported into the cytosol, either by direct plasma membrane penetration or after endocytosis. This discussion includes comments about pitfalls when using pharmacological inhibitors in such studies. The possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 39 publications
0
35
0
2
Order By: Relevance
“…[21][22][23] Cell-penetrating peptides (CPPs) are small peptides that cross the cell membrane readily and can be attached to various cargos to deliver molecular material inside the cells. [24][25][26] For example, octaarginine has been attached to Ru II complexes and efficiently enhanced the internalization of the tethered complexes. [23,27] We have demonstrated that DNA-photoreactive Ru-TAP complexes conjugated to specific antisense oligonucleotides and internalized into living cells by particular synthetic polymers specifically inhibit the expression of targeted genes.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Cell-penetrating peptides (CPPs) are small peptides that cross the cell membrane readily and can be attached to various cargos to deliver molecular material inside the cells. [24][25][26] For example, octaarginine has been attached to Ru II complexes and efficiently enhanced the internalization of the tethered complexes. [23,27] We have demonstrated that DNA-photoreactive Ru-TAP complexes conjugated to specific antisense oligonucleotides and internalized into living cells by particular synthetic polymers specifically inhibit the expression of targeted genes.…”
Section: Introductionmentioning
confidence: 99%
“…CPPs, also known as proteintransduction domains, are short, basic peptides that are capable of entering cells without the need of a specific receptor [33]. Fusion of CPPs, such as HIV-1 Tat peptide or HSV VP-22 peptide, to other proteins has been used to deliver a variety of proteins to living cells [34]. Although CPPs represent an emerging tool for protein drug delivery, some disadvantages exist including susceptibility to cleavage by plasma enzymes, low efficiency to deliver large cargos, and likelihood of causing severe toxicity to kidney and liver [35].…”
Section: Discussionmentioning
confidence: 99%
“…16,23) Many CPPs, including HIV-Tat peptide, have many positively charged amino acids such as arginine and, when penetrating into cells, are bound to the HSPG on the cell surface. 24) Furthermore, CPPs composed of hydrophobic amino acids have also been reported, and various peptides are used as CPPs. 25) Peptide C has no bias in certain positively charged amino acid residues and interacts with trypsin-sensitive molecules on the surface of K562 cells.…”
Section: Discussionmentioning
confidence: 99%